P-Moment Exponential Stability of Caputo Fractional Differential Equations with Random Impulses - Agarwal, Ravi; Hristova, Snezhana; O’Regan, Donal (Discontinuity, Nonlinearity, and Complexity, 2026)
Fractional differential equations with random impulses arise in modeling real world phenomena where the state changes instantaneously at uncertain moments. Using queuing theory and the usual distribution for waiting time, we study the case of exponentially distributed random variables between two consecutive moments of impulses. The p-moment exponential stability of solutions is defined and studied when the waiting time between two consecutive impulses is exponentially distributed. The argument is based on Lyapunov functions. We discuss both continuous and differentiable Lyapunov functions and Caputo fractional Dini derivatives and Caputo derivatives are applied. Some examples are given to illustrate our results.